The Role of the Regional Notary Honorary Council in Guiding and Supervising the Notary Code of Ethics in Pekanbaru City - Pujiono, Arik (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This research aims to determine and analyze the role of the Notary's Regional Honorary Council (DKD) in providing guidance and supervision to Notaries who violate the Notary's Code of Ethics and how to enforce sanctions against violators of the Notary's Code of Ethics by the Notary's Regional Honorary Council in the city of Pekanbaru. In this research, the author uses empirical legal research. The empirical legal research method is legal research which functions to see the law in real terms and examine how the law works in society. The structural approach method is a method or approach to the operation of law in society based on the structures found in society. data structure approach obtained directly from respondents (research objects). The type of data used in this research is primary data. The analysis in this research is descriptive. Descriptive means that in analyzing the author the desire is to provide an overview or presentation of the research results. Collecting research data using direct interview techniques from the source, namely the Regional Honorary Council of Notaries in Pekanbaru City. The results of the research show that the Regional Honorary Council for Notaries in the city of Pekanbaru, in its supervision and guidance as well as providing sanctions, has not been effective, with the discovery of Notaries who still violate the Notary Code of Ethics stipulated in Law Number 2 of 2014 concerning amendments to Law No. 30 of 2004 concerning the position of Notary.